Amerykański przyjaciel? Problem granic Polski w kontaktach ambasadora Anthony’ego J. Drexela Biddle’a z rządem Władysława Sikorskiego w latach 1941–1943 - Siwek, Krzysztof (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article deals with Polish borders and territorial issues seen from the perspective of the United States Ambassador to Poland Anthony J. Drexel Biddle’s contacts with the government of Wladyslaw Sikorski in 1941–1943. The aim of the article is to present, on the basis of American and Polish archival materials, the American assessment of Polish border issues, as well as the expectations of the Polish government towards the United States and Western allies regarding territorial issues, particularly against the background of the Polish-Soviet relations evolving since 1941.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne